Synthesis and Spectral Studies of Some Azo Polyimides - Rajendiran, T.V.; Anbuchelvan, C. (Asian Journal of Chemistry, 2010)
Ten polyimides based on p,p'-aromatic diamines and 3,3', 4,4'-azo benzenetetracarboxylic dianhydride were synthesized by high temperature solution imidization method. The polymers were characterized by viscosity, solubility, UV-Visible, IR, Raman spectroscopy and thermogravimetry.